Stagnation of Mobile Court Services and Access to Justice in Remote Island Communities: Evidence from the Religious Court of Labuha, Indonesia - La Tua, Mujaidin; Husain, Muhammad Ar.; Alhadar, Muhdi (ANTMIND YOUTH EMPOWER FOUNDATION, 2025)
Access to justice remains a major challenge for communities living in remote and geographically isolated regions, particularly in archipelagic states such as Indonesia. Mobile court services (sidang keliling) have been established as a judicial outreach mechanism to improve access to legal services for marginalized populations. This study examines the stagnation of mobile court implementation at the Religious Court of Labuha and its impact on the resolution of Islamic family law cases in Pulau Taliabu Regency. Using a qualitative socio-legal research approach, data were collected through in-depth interviews with judges, court officials, and officers of the Office of Religious Affairs, supported by field observations and analysis of institutional documents and case records. The findings show that mobile court services in Pulau Taliabu were effectively inactive between 2018 and 2022 due to limited judicial personnel, weak inter-institutional coordination, budgetary constraints, and geographical barriers. This stagnation resulted in the accumulation of family law cases, particularly divorce and marriage legalization (isbat nikah), thereby restricting procedural efficiency and substantive access to justice for local communities. The study further demonstrates that the resumption of mobile court services in early 2023 significantly improved case resolution and legal accessibility. Normatively, these findings underscore the relevance of maṣlaḥah mursalah as an ethical-legal framework that emphasizes public benefit, harm prevention, and judicial accessibility. This article contributes to the broader discourse on access to justice and judicial reform by highlighting the importance of sustainable mobile court mechanisms for remote island communities.